Aerobic oxidative homocoupling reaction of anilides using heterogeneous metal catalysts. Issue 10 (8th March 2017) - Fujimoto, Shigenobu; Matsumoto, Kenji; Iwata, Takayuki; Shindo, Mitsuru
Graphical abstract: Highlights: We have developed the first heterogeneous metal-catalyzed oxidative homocoupling reaction of dimethoxyanilides. This reaction can be carried out under oxygen as a co-oxidant. The reaction conditions are very mild. Abstract: We have developed a heterogeneous catalytic oxidative homocoupling reaction of dimethoxyanilides under an oxygen atmosphere. The resulting homo-dimers are useful for the construction of heterocycles, demonstrating the potential of heterogeneous metal catalysts.